The human rights treaty obligations of peacekeepers / Kjetil Mujezinović Larsen. - Larsen, Kjetil Mujezinović, 1976- (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2012)
Do States, through their military forces, have legal obligations under human rights treaties towards the local civilian population during UN-mandated peace operations? It is frequently claimed that it is unrealistic to require compliance with human rights treaties in peace operations and this has led to an unwillingness to hold States accountable for human rights violations. In this book, Kjetil Larsen criticises this position by addressing the arguments against the applicability of human rights treaties and demonstrating that compliance with the treaties is unrealistic only if one takes an 'all or nothing' approach to them. He outlines a coherent and more flexible approach which distinguishes clearly between positive and negative obligations and makes treaty compliance more realistic. His proposals for the application of human rights treaties would also strengthen the legal framework for human rights protection in peace operations without posing any unrealistic obligations on the military forces.